THE INFLUENCE OF DIGITAL MARKETING ON CONSUMER BUYING INTEREST IN THE HALUA SRI LANGKAT CANDY BUSINESS IN NORTH SUMATERA - Aina Salsabila Qarnain Br. Bangun; Maisyura; Riyandhi Praza; Sufi; Nursanjaya (RADJA PUBLIKA, 2025)
The right marketing and media strategies are needed to reach a wider market so that it can attract consumer interest, one of which is digital marketing. Digital marketing is a marketing media that is currently in great demand by the public to support various activities carried out. This study was conducted to determine the effect of digital marketing on consumer purchasing interest in the Sri Langkat Halua Candy Business. This study isdescriptive quantitative research using 96 samples determined based on the Lemeshow formula with non-probability sampling techniques. Data analysis used in this study using simple linear regression with the help of the SPSS 25.0 software program. The types of data testing used in this study include data instrument testing, classical assumption testing, and hypothesis testing. The results of the study indicate that digital marketing has a positive and significant effect on consumer buying interest in the Sri Langkat Halua Candy Business.This means that implementing digital marketing can provide a stimulus to generate consumer purchasing interest.While the R value is 38.8% where the correlation coefficient value shows the influence of digital marketing on consumer purchasing interest in the Halua Sri Langkat Candy Business in the low category. The determination coefficient value or R square value shows that 15% can be explained by the digital marketing variable, the rest is explained by other variables not included in this study.